2014
DOI: 10.11138/ccmbm/2014.11.1.025
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid nuclear scan. A focused review on the technical and biological factors affecting its outcome

Abstract: Conclusion.Clinicians should be aware of technical and biological factors that could result in negative scan in parathyroid nuclear scintigraphy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Similarly, among the patients having positive scan 62.2% (n=23) had serum calcium level greater than 12.3 mg/dL as opposed to 37.8 % (n=14) in those with lower level. Among 18 false negative cases, five (27.7 %) had The degree of hypercalcaemia in primary hyperparathyroidism seems to be closely related to defective regulation of PTH secretion, metabolic rate and elevated membrane potential rather than increased mass of parathyroid tissue (5). Indeed, in some patient hypercalcaemia may be surprisingly increased despite only modest glandular enlargement.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, among the patients having positive scan 62.2% (n=23) had serum calcium level greater than 12.3 mg/dL as opposed to 37.8 % (n=14) in those with lower level. Among 18 false negative cases, five (27.7 %) had The degree of hypercalcaemia in primary hyperparathyroidism seems to be closely related to defective regulation of PTH secretion, metabolic rate and elevated membrane potential rather than increased mass of parathyroid tissue (5). Indeed, in some patient hypercalcaemia may be surprisingly increased despite only modest glandular enlargement.…”
Section: Resultsmentioning
confidence: 99%
“…In a study on the factors affecting MIBI localization, Kannan et al found that higher serum calcium and serum PTH levels were associated with a higher likelihood of a positive scan (5). For this reason, we used preoperative PTH values as one criteria to match +LT and −LT patients.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this assumption, MIBI uptake within the parathyroid gland could be related to cell types like chief cells with high metabolic activity and/or oxyphil cell with many mitochondria. However, clear cell and adipose cell thought to have no significant role in MIBI uptake [5][6] . In this study the overall sensitivity of MIBI scan was 67.2% which is low compare to other reported sensitivity of 75-80% 1 .…”
Section: Discussionmentioning
confidence: 99%